Monthly quasi-periodic eruptions from repeated stellar disruption by a massive black hole - Evans PA; Nixon CJ; Campana S; Charalampopoulos P; Perley DA; Breeveld AA; Page KL; Oates SR; Eyles-Ferris RAJ; Malesani DB; Izzo L; Goad MR; et al. (NATURE PORTFOLIO, 2025)
In recent years, searches of archival X-ray data have revealed galaxies exhibiting nuclear quasi-periodic eruptions with periods of several hours. These are reminiscent of the tidal disruption of a star by a supermassive black hole. The repeated, partial stripping of a white dwarf in an eccentric orbit around an ~105 M⊙ black hole provides an attractive model. A separate class of periodic nuclear transients, with much longer timescales, have recently been discovered optically and may arise from the partial stripping of a main-sequence star by an ~107 M⊙ black hole. No clear connection between these classes has been made. We present the discovery of an X-ray nuclear transient that shows quasi-periodic outbursts with a period of weeks. We discuss possible origins for the emission and propose that this system bridges the two existing classes outlined above. This discovery was made possible by the rapid identification, dissemination and follow-up of an X-ray transient found by the new live Swift-XRT transient detector, demonstrating the importance of low-latency, sensitive searches for X-ray transients.